Neoliberalism or Democracy: Competing Forms of Social Organization in Latin America - Dowd, Jeffrey (Conference Papers -- American Sociological Association, 2007)
While political turmoil is not new to Latin America, the tension between neoliberalism and democracy can help explain present-day turmoil. The current political situation in Latin America is the result of a disconnect between the goals of democracy, in particular, between social justice goals, upon which the legitimacy of democratic government rests, and the neoliberal economic policy of the region. Polanyi's concept of the always-embedded economy states that a market economy must be embedded in a market society. Following Polanyi, I argue that markets and democracy require different forms of social organization. Markets and democracy are alternate and competing forms of social organization. The predominance of one often coincides with the restriction of the other. For example, neoliberal governance that maintains market society undermines electoral efficacy. While this may be a general attribute of neoliberalism, previous economic crisis in Latin America increased the need for rhetorical commitment to social justice goals. Latin America's structural position has not changed, however, and international finance and global organizations, like the International Monetary Fund and the World Bank, still constrain Latin American governments. I argue that any resolution to the tension between neoliberalism and democracy must accept the conflicting nature of these two forms of social organization. ..PAT.-Unpublished Manuscript
Keywords: Latin America; always embedded economy; democracy; economic policy; embeddedness; free market; free-market; market; neoliberalism; political science; political theory; social justice